Peran Pemangku Kepentingan Rantai Pasokan Pariwisata dalam Pengembangan Kepariwisataan Desa Sedari - Kevin Rais Rachman; Owen Edwardlis; Myrza Rahmanita; Heny Ratnaningtyas Heny (Tourism Scientific Journal, 2021)
Sedari Village is a  tourism village in Karawang Regency which  has developed quite significantly yet has not been optimalize the roles of its stakeholders The success of a tourism destination is typically determined by the role and collaboration amongst  stakeholders. Using qualitative method, this study is conducted to explore the role of stakeholders in developing tourism potential in Sedari village. The findings of this study show that a number of obstacles and problems exist related to public awareness, accessibility, local conflicts, components of tourist destinations. Secondly, this research demonstrates that each stakeholder carry out their roles, initiatives and interests separately. It is recommended that stakeholders synergize in producing outputs with a shared focus in accordance with the Sedari village strategic tourism development path. Another recommendation is for the Local and Regional Government to take the initiative to collaborate with other stakeholders while accepting the presence of stakeholders in their respective initiatives.